Xyloneside A: A New Glycosylated Incisterol Derivative from Xylaria sp. FB. (5th May 2020) - Lee, Seoung Rak; Kreuzenbeck, Nina B.; Jang, Mina; Oh, Taehoon; Ko, Sung‐Kyun; Ahn, Jong Seog; Beemelmanns, Christine; Kim, Ki Hyun
Abstract: Xylaria species are prolific natural product producers. Here, we report the characterization of a new glycosylated incisterol derivative, called xyloneside A (1 ) and two known lignans (2 and 3 ) from the ascomycetous Xylaria sp. FB. The structure of xyloneside A (1 ) was determined by 1D and 2D NMR spectroscopy, high‐resolution electrospray ionization mass spectrometry and electronic circular dichroism measurements. Xyloneside A is composed of a 1, 2, 3, 4, 5, 10, 19‐heptanorergosterane skeleton and a β ‐ D‐mannopyranose moiety. This is the first report of an incisterol derivative from an Ascomycete. The biological effects of the isolated metabolites on cytotoxicity, autophagy, cell‐migration, and angiogenesis were evaluated. Abstract : Glycosylated incisterol derivative xyloneside A has been isolated from an ascomycetous Xylaria hypoxylon species – a prolific fungal species. The structure was determined by spectroscopy, and its pharmacological properties were evaluated. Identification of fungal incisterols and ergosterol derivatives could lead to potential new antifungal drug scaffolds.